Pengembangan Magic Box Terkoneksi Quick Response Code dan Padlet untuk Pembelajaran Pengolahan Data di Sekolah Dasar - Zaid Zainal; Nurul Mukhlisa; Dian Rahmani (Program Studi Pendidikan Matematika, FKIP Universitas Muslim Maros, 2025)
This research is a research and development using the ADDIE development model. This model consists of five stages, namely analysis, design, development, implementation, and evaluation. The purpose of this research is to develop media needed by teachers and students in Mathematics learning, especially data processing materials, and to test the validity of developed media. The result of the needs analysis indicate that students' low numeracy skills in data processing learning are evident from the results of observations, tests, and questionnaires. The result of the design and product characteristics produce a representation of learning media that attracts students' attention with a combination of multimedia. The result of validity test by material expert show that the media is included in the very feasible category (83,3%), by media experts in the very feasible category (100%). The summary of the findings of media user questionnaire shows that the media is very feasible to be used in learning both according to students (89%) and teachers (99%). This development of Magic Box connected to Quick Response Code and Padlet for learning in elementary schools as an alternative new strategy in technology-based Mathematics transformation.